Dari Galeri Ke Kedai: Komodifikasi Batik Di Keris Café Solo Dan Adaptasi Budaya Visual Dalam Ruang Konsumsi Milenial - Denik Ristya Rini; Hartono Hartono; Eko Raharjo (Institut Seni Indoensia Surakarta, 2025)
Batik is a traditional Indonesian art that continues to be maintained and developed by the community from time to time. In maintaining the existence of batik art, of course there are many challenges faced by batik traders. To respond to this, batik business actors are required to be creative and innovative in creating strategies in carrying out innovation so that people have the desire to come to their showrooms. Based on observations made in the city of Solo, namely in the Keris Café Solo and Keris Café Solo areas, there is an interesting phenomenon that occurs in the sustainability of the batik business. This is an interesting theme to study about how the commodification of the batik industry in the city of Solo. The approach used in this study is descriptive qualitative and cultural study perspective. This study explores how traditional art is contextualized into contemporary consumption spaces. The findings show that this commodification is not only a strategy, but also a form of cultural expression that is relevant to art education and the involvement of the younger generation in cultural heritage.